2011
DOI: 10.1097/ncc.0b013e3181f04ae9
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Trajectories in Posttreatment Cancer Survivors

Abstract: The posttreatment surveillance plan for cancer survivors should include a comprehensive assessment of psychological and physical symptoms. Persistence of symptoms can be expected in some patients, and supportive interventions should be tailored according to symptom reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 49 publications
3
42
0
1
Order By: Relevance
“…As seen in previous research (e.g., (Barbera, et al, 2010; Philip, Merluzzi, Zhang, & Heitzmann, 2012)), women reported a higher concern burden than men, and younger survivors reported more physical, emotional, and employment concerns (Bloom, Petersen, & Kang, 2007; Brant et al, 2011; Foster, Wright, Hill, Hopkinson, & Roffe, 2009; Mao et al, 2007; Meyerowitz, Kurita, & D'Orazio, 2008; Shi, et al, 2011; Smith, Crespi, Petersen, Zimmerman, & Ganz, 2010; B. J. Zebrack, Yi, Petersen, & Ganz, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…As seen in previous research (e.g., (Barbera, et al, 2010; Philip, Merluzzi, Zhang, & Heitzmann, 2012)), women reported a higher concern burden than men, and younger survivors reported more physical, emotional, and employment concerns (Bloom, Petersen, & Kang, 2007; Brant et al, 2011; Foster, Wright, Hill, Hopkinson, & Roffe, 2009; Mao et al, 2007; Meyerowitz, Kurita, & D'Orazio, 2008; Shi, et al, 2011; Smith, Crespi, Petersen, Zimmerman, & Ganz, 2010; B. J. Zebrack, Yi, Petersen, & Ganz, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…8 In lung cancer, CRC, and lymphoma survivors, physical symptoms of pain, fatigue, and sleep disturbance combined with psychological symptoms of distress and depression have been reported to persist for up to 16 months after the initial chemotherapy treatment. 9 Furthermore, the self-efficacy of CRC patients after the onset of chemotherapy has been associated with declines in work ability and decision making, implying social and financial impairments for affected patients. 10 Thus, comprehensive assessment and treatment of both physical and psychological symptoms, especially in the early stages of the treatment, are necessary to avoid progressive worsening of depression.…”
mentioning
confidence: 99%
“…Survivors continue to experience significant limitations, compared to those without a history of cancer [4]. The presence of symptoms persists permanently, resulting from the direct adverse effects of cancer, treatment, exacerbation and/ or onset of new ones, associated with recurrence or second tumor [5,6].…”
Section: Introductionmentioning
confidence: 99%